Financial Capability Index on Regencies and Cities in Indonesia - Putri, Phany Ineke; Sa’adah, Syifa Sa’adah (Salam (Islamic Economics Journal), 2024)
This study aims to analyze the effect of the Local Own Revenue and General Allocation Fund on district and city regional expenditures in Indonesia, in addition to analyzing the flypaper effect that occurs in regencies/cities in Indonesia on the Low, Medium, and High Financial Capability Index.The data used is secondary data and uses multiple regression analysis with a combination of time-series data from 2017 to 2021 and cross-section data consisting of 499 districts and cities. The result shows that Local Own Revenue and General Allocation Fund have positive significant effect on regional expenditures, an increasing in Local Own evenue will increase regional expenditures. Transfers from the central government will be responded to by increasing regional spending. This shows that local governments are still dependent on the General Allocation Fund.30 Regencies/cities in Indonesia with a low classification of Financial Capability Index (IKK) proved to be a flypaper effect phenomenon, while 187 districts/cities with a medium classification of Financial Capability Index (IKK), and 282 regencies/cities there is a flypaper effect on the financial capability index at a high level.